Desain Media PowerPoint Interaktif Berbasis Animasi Materi Pancasila sebagai Nilai Kehidupan untuk Siswa Kelas IV Sekolah Dasar - Lapebridinsi, Clara; Oktaria, Sesmita; Nabila, Syahira (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2023)
This research was motivated by the low student learning outcomes. This is because some teachers consider this learning media to be less important, and still use conventional learning media. This research aims to describe the development of interactive PowerPoint media based on animation on Pancasila regarding elementary school student learning outcomes. The research model used was the ADDIE model which consists of analysis, design, development, implementation, and evaluation. The media was tested in a small group of students and the results show that the use of interactive PowerPoint media can improve student learning outcomes in teaching and learning activities, help eliminate boredom, and motivate student learning.